Rel-dependent decrease in the expression of ribosomal protein genes by inhibition of the respiratory electron transport chain in Mycobacterium smegmatis - Kim, Na-Kyeong; Baek, Jong-Eun; Lee, Ye-Jin; Oh, Yuna; Oh, Jeong-Il (Frontiers in Microbiology, 2024)
In this study, we demonstrated that both the expression of most ribosomal protein genes and the amount of ribosomes were decreased in the aa3 mutant of Mycobacterium smegmatis, in which the major terminal oxidase (aa3 cytochrome c oxidase) of the respiratory electron transport chain (ETC) is inactivated, compared to those in the wild-type strain. Deletion of the rel gene encoding the major (p)ppGpp synthetase in the background of the aa3 mutant restored the reduced expression of ribosomal protein genes, suggesting that inhibition of the respiratory ETC leads to the Rel-dependent stringent response (SR) in this bacterium. Both a decrease in the expression of ribosomal protein genes by overexpression of rel and the increased expression of rel in the aa3 mutant relative to the wild-type strain support the Rel-dependent induction of SR in the aa3 mutant. We also demonstrated that the expression of ribosomal protein genes was decreased in M. smegmatis exposed to respiration-inhibitory conditions, such as KCN and bedaquiline treatment, null mutation of the cytochrome bcc1 complex, and hypoxia. The MprBA-SigE-SigB regulatory pathway was implicated in both the increased expression of rel and the decreased expression of ribosomal protein genes in the aa3 mutant of M. smegmatis.